Does early goal directed therapy in sepsis still hold relevance in low and middle-income countries? - Aryal, Diptesh; Sharma, Apurb (Journal of Society of Anesthesiologists of Nepal, 2017)
The efficacy of early goal directed therapy in improving outcomes has been questioned in few recent studies. But, does that hold true for low and middle income countries like Nepal? This editorial expresses the views of the editors on the usual care of sepsis patients and early goal directed therapy in resource limited settings.